PENJATUHAN SANKSI ADAT MELEKAT NE BIS IN IDEM - Kosmas, Amajihono (JURNAL PANAH KEADILAN, 2024)
In Indonesia, especially in some areas, people still uphold the value of customs when carrying out several activities. Such as traditional ceremonies if you want to hold a wedding, funeral ceremonies, and even when someone commits an immoral act, customary punishment will be carried out on the perpetrator. Each region has its own historical and cultural background and this also influences the implementation of punishment according to the beliefs that apply in each region. The state, which is a powerful social organization, has the obligation to regulate so that security is guaranteed and there is protection for the interests of each person, and so that equal happiness is achieved in society. In Article 27 paragraph (1) of the 1945 Constitution (UUD 1945) it is stated that all citizens have the same position under the law and government and are obliged to uphold the law and government without exception. Then Article 5 paragraph (3) Law no. 39 of 1999 concerning Human Rights which confirms the following: (1) Every person is recognized as an individual human being who has the right to demand and obtain equal treatment and protection in accordance with his or her human dignity before the law. (2) Everyone has the right to receive fair assistance and protection from an objective and impartial court. (3) Every person belonging to a vulnerable group of people has the right to receive more treatment and protection with regard to their specific characteristics.